Heterozygous de novo mutation in the ATP1A2 gene in a patient with alternating hemiplegia of childhood - Wojciechowska, Katarzyna; Pikulicka, Agata; Drgas, Olga; Brudkowska, Żaneta; Żarnowska, Iwona (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Alternating hemiplegia of childhood (AHC) is characterized by recurrent hemiplegic episodes and paroxysmal disorders, dystonia, nystagmus, epileptic seizure, mental retardation, and intellectual impairment. Alternating hemiplegia of childhood is caused by pathogenic variants in the genes encoding α-1, -2, and -3 subunits of Na,K-ATPase. Among them, pathogenic variants in ATP1A3 are responsible for almost 80% of cases. The aim of our study was to present a patient with de novo ATP1A2 mutation as the primary cause of AHC and to study the spectrum of phenotypes associated with mutation in this gene. Our study presents a case of a 9-year-old boy who was correctly diagnosed with AHC at the age of 8 years. The example of our patient proves that pathogenic variants in ATP1A2 correlate with milder phenotype.